Mass killings around the world and the risks associated with civilian arms trafficking - Bozadzhyiev , Illya (Actual problems of law (Aktual'ni problemi pravoznavstva), 2025)
The article analyzes the experience of different countries and the preparation of criminals for mass murder. It is noted that mass murders can be committed using various means of destruction. In addition to firearms, these include knives, ammonium nitrate, chemicals, etc. Easy access to the Internet facilitates offenders in achieving their criminal goals. Mass murderers did not target hard-to-reach places for terrorist attacks. The primary locations of terrorist attacks were areas where it is prohibited to carry or use firearms, such as schools, children's entertainment centers, and colleges. In the English-speaking scientific community, these zones are referred to as «gun-free zones». The issue of so-called «mass shootings» is not unique to the United States or other countries with liberal gun laws. Czech scholar Alexei Anisin has also pointed out the common features of mass killings, highlighting this problem as an international threat at the level of domestic terrorism. Particular attention to the domestic legal situation in the United Kingdom of Great Britain and Northern Ireland, a country that, since the mid-1990s, has been pursuing a consistent policy of removing weapons from civilian circulation. Citing statistics from the UK Parliament, a trend of increasing offenses involving bladed weapons over 13 years (2010-2023) was identified. In 2024, a mass murder committed by 17-year-old Axel Muganwa Rudakuban, a Welsh national and British citizen, led to widespread unrest. The UK government convened urgently to address this situation as a matter of national security.  The article presents the positive experience of a civil society organization and the 4-H program of the same name (USA) in civilian firearms training for children and adolescents. The author provides internal statistics showing that sport shooting results in fewer injuries compared to contact sports for children.  The article revisits the long-standing debate on the legal uncertainty of Ukraine's arms legislation, particularly the absence of a law regulating civilian weapons and self-defense. The author analyses the opposing views of Ukrainian scholars on the civilian circulation of guns and revolvers. The issue of promoting a gun culture, tactical medicine courses, and safe handling of weapons in Ukraine.